First report of Bemisia tabaci Mediterranean (Q biotype) species in Brazil - Barbosa, Leonardo da Fonseca [UNESP]; Yuki, Valdir Atsushi; Marubayashi, Julio Massaharu [UNESP]; De Marchi, Bruno Rossitto [UNESP]; Perini, Fernando Luis; Pavan, Marcelo Agenor [UNESP]; Barros, Danielle Ribeiro de; Ghanim, Murad; Moriones, Enrique; Navas-Castillo, Jesus; Krause-Sakate, Renate [UNESP] (Wiley-Blackwell, 2015)
BACKGROUND: The whitefly Bemisia tabaci is amajor cosmopolitan pest and comprises a complex of more than 36 cryptic species that cause serious damage to agricultural crops worldwide. In this study, the Mediterranean species of B. tabaci, formerly known as Q biotype, was identified for the first time in Brazil.RESULTS: Adult B. tabaci were collected from different localities and hosts from Rio Grande do Sul, the southernmost state of the country that borders Uruguay and Argentina. Partial sequencing of the mitochondrial cytochrome oxidase I (mtCOI) gene indicated that B. tabaci MED species appears to be restricted to the province of Barra do Quarai, infesting Capsicum annuum cultivated in greenhouses and Ipomoea batatas in open fields. The partial mtCOI sequences obtained shared 100% nucleotide identity with reference sequences for the Q biotype reported from Uruguay. The secondary endosymbionts Hamiltonella and Cardinium were detected by PCR in the new identified MED species from Brazil, similarly to the Q biotype from Uruguay.CONCLUSION: Our results indicate the presence of the MED species in Brazil. The close monitoring of this new identified species in the southern region of Brazil is essential to avoid its geographical expansion to more important agricultural areas in the country. (C) 2014 Society of Chemical Industry
Keywords: Bemisia tabaci; MED species; Invasion; Whitefly